2018
DOI: 10.1016/j.ebiom.2018.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial – nuclear genetic interaction modulates whole body metabolism, adiposity and gene expression in vivo

Abstract: We hypothesized that changes in the mitochondrial DNA (mtDNA) would significantly influence whole body metabolism, adiposity and gene expression in response to diet. Because it is not feasible to directly test these predictions in humans we used Mitochondrial-Nuclear eXchange mice, which have reciprocally exchanged nuclear and mitochondrial genomes between different Mus musculus strains. Results demonstrate that nuclear-mitochondrial genetic background combination significantly alters metabolic efficiency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 41 publications
0
47
0
Order By: Relevance
“…From this mito-Mendelian perspective, variants within mitochondrial genes in both genomes, nuclear and mitochondrial, likely modify the responses of the mitochondrion to stimuli such as endogenous or exogenous factors (e.g., cytokines or environmental factors, respectively), and therefore represent an area that, as of yet, remains largely unexplored. Further, these studies and others (810) strongly suggest the need for greater contemplation of how to interpret results from experiments utilizing genetic models having different mtDNA backgrounds. In fact, mitochondrial genetic diversity may be a key missing link in our understanding of how genetic–environmental interactions impact disease risk, in that it would now include a mito-Mendelian perspective.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…From this mito-Mendelian perspective, variants within mitochondrial genes in both genomes, nuclear and mitochondrial, likely modify the responses of the mitochondrion to stimuli such as endogenous or exogenous factors (e.g., cytokines or environmental factors, respectively), and therefore represent an area that, as of yet, remains largely unexplored. Further, these studies and others (810) strongly suggest the need for greater contemplation of how to interpret results from experiments utilizing genetic models having different mtDNA backgrounds. In fact, mitochondrial genetic diversity may be a key missing link in our understanding of how genetic–environmental interactions impact disease risk, in that it would now include a mito-Mendelian perspective.…”
mentioning
confidence: 92%
“…In Drosophila melanogaster , exposure to hypoxia induced gene expression changes that differed by mitochondrial haplotype, suggesting that environmental exposures impact mitochondrial signaling responses differently based upon the mitochondrial haplotype (7). Similarly, a series of studies utilizing mitochondrial−nuclear exchange models, wherein different mtDNA genetic backgrounds were paired with the same nuclear genetic background, have directly shown that disease susceptibility, bioenergetic function, oxidant production, and, importantly, gene expression are significantly changed in vivo (810). Importantly, the findings of Kopinski et al (1) provide a likely explanation for these observed differences in that they link mtDNA genetics with nuclear epigenomic modulation via changes in metabolic intermediates—further providing evidence of systemic molecular mechanisms that are defined by mtDNA genetics, which modulate transcriptional control of the nuclear genome.…”
mentioning
confidence: 99%
“…These “mito-Mendelian” genetic interactions enabled genetic adaptation to change in environment by modulating the utilization of electron flow molecular and thermal energy (ATP and heat), and signaling (oxidants and metabolites) important for survival (Figure 1). This paradigm for explaining the genetic – physiologic basis in medicine remains controversial despite a growing number of studies showing the impact of different mtDNA backgrounds on disease, using both in vitro and in vivo approaches (Dunham-Snary et al, 2018; Fetterman et al, 2013; Ishikawa et al, 2008). Early studies in the cancer literature were among the earliest reports showing the influence of the mtDNA on tumor growth and metastasis using in vitro approaches (Ishikawa et al, 2008; Petros et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These interactions can be demonstrated experimentally in the Mitochondrial – Nuclear eXchanged (MNX) models. These systems directly generate reciprocal combinations of different mtDNA-nuclear DNA combinations and have shown that mtDNA background significantly influences disease development in mice having isogenic nuclear backgrounds in vivo (Dunham-Snary et al, 2018; Fetterman et al, 2013). They also provide evidence that mtDNA – nDNA combination can be important for overall mitochondrial “economy” and thus, impacts organelle bioenergetic efficiency and oxidant generation (Fetterman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation